Analysis of the Effect of Perceived Ease of Use, Perceived Usefulness and Perceived Security on Intention to Use Brimo Mobile Banking with Trust as Mediation - Wijanarko, Muhammad Fuad; Sihite, Janfry (Indonesian Journal of Business Analytics, 2024)
This study aims to identify the condition of each variable, namely perceived ease of use, perceived usefulness, and perceived security, as well as the intention to use Brimo mobile banking. In addition, this study was conducted to analyse and test the impact of perceived ease of use, perceived usefulness, and perceived security on intention to use. This type of research is included in the descriptive research category, which is carried out through the explanatory survey method by distributing questionnaires to 100 Brimo application users in the Jabodetabek area and outside Jabodetabek who have used the Brimo application at least twice. The analytical tool used to process data is variant-based Structural Equation Modelling (SEM) using Smart-PLS. The findings of this study indicate that perceived ease of use, perceived usefulness, and Perceived Security have a positive and significant influence on intention to use. However, the results also show that trust cannot be considered as a mediator between perceived ease of use, perceived usefulness, and perceived security with intention to use.